An impact study of acoustic environment on users in large interior spaces. Issue 2 (June 2019) - Chen, Jing; Ma, Hui
As many large buildings have been built worldwide recently, it is necessary to study how the acoustic environment in those buildings affects people in order to improve the acoustical comfort in them. The aim of this study is to explore the influence of acoustic environment on people in eight large-scale spaces, which are divided into three categories according to function, through grounded theory, and questionnaire. The results showed that "loud background noise, " "large number of sound sources, " "emotional change, " "mixed sounds, " and "sensible sound with certain spectrum component" were people's main evaluation to the acoustic environment in large-scale spaces. Based on respondents' perception, the influence of the acoustic environment in large-scale spaces could be classified into the following three aspects: emotional effect, influence on attention, and influence on thinking ability and behavior. Although the evaluation of the acoustic environment varied widely with the difference in spatial functions, same perception dimensions could be summarized.